Evaluation of the World Health Organization outcome standards at the early and late post-operative visits following cataract surgery - Meyer, Jay J; Murray, Neil L (Nepalese Journal of Ophthalmology, 2020)
Introduction: This study was conducted to determine whether the World Health Organization (WHO) visual acuity standards are correlated between the early and late early post-operative periods following phacoemulsification (phaco) and small incision extracapsular cataract surgery (SICS). Secondary aims were to compare visual outcomes and complications following SICS and phaco. Methods: Retrospective cohort study following phaco and SICS performed by one surgeon. Primary outcome measures included uncorrected visual acuity (UCVA) and best corrected visual acuity (BCVA) at the early (≤72 hours) and late (≥21 days) post-operative visits. Secondary outcome measures included complications and astigmatism. Results: 705 eyes were studied (509 phaco, 196 SICS). The correlation for UCVA between early and late follow-up examinations was higher for phaco (rs=0.58) compared to SICS (rs=0.45, p=0.04) while correlation for BCVA was similar (phaco,rs=0.52; SICS, rs=0.47; p=0.44). At the early post-operative visit, a higher proportion in the phaco group achieved ≥6/18 UCVA (81.5% phaco vs 64.8% SICS, p<0.0001) and BCVA (87.8% phaco vs 73.5% SICS, p<0.0001). At the late post-operative visit, a higher proportion following phaco also achieved ≥6/18 UCVA (93.9% phaco vs 85.2% SICS, p=0.0004) and BCVA (96.9% phaco vs 91.3% SICS, p=0.004). After exclusion of eyes with pre-existing ocular comorbidities, a similar proportion had ≥6/18 late UCVA (98.9% phaco vs 96.9% SICS, p=0.22) and BCVA (100% phaco vs 99.2% SICS, p=0.27). Conclusions: Early and late post-operative WHO visual acuity levels are correlated, but not equivalent, following both phaco and SICS. In eyes without comorbidities, similar final visual outcomes can be achieved after phaco and SICS.